IMPROVEMENT OF BENDING STRENGTH FOR INERT GAS WELD JOINT ALUMINUM ALLOYS 6061-T6 USING SHOT PEENING - Mohsein, Z.H. (Journal of Advanced Manufacturing Technology (JAMT), 2015)
The present study aims at investigating the effect of MIG welding process on the bending strength of aluminum alloys 6061 -T6. Metal inert gas (MIG) has been carried out on rolled sheet of about 8mm thickness to obtain many butt welding joints with dimension of (200 *100* 8) mm with welding preparation angle in the shape of single V of 65⁰ and double V of 65° weld joint by ER- 4043(Al-Si5) as a filler metal and argon as a shielded gas. The welded joints were tested by X-ray radiography and faulty pieces were excluded, i.e., the welding joint were subjected to heat treatment including heating the joint in furnace to 150°C for about half an hour, followed by air cooling to relief welding stress. Several specimens were machined into standard test specimen dimensions according to the ASTM (E 190-92). Some of the specimens were then subjected to shot peening process for 15 minutes using a steel ball with a diameter of 1.25 mm. Vickers hardness test and microstructure examination were made. The results of the current study show a general decay of bending strength of MIG weld joint in comparison with unwelded metal due to the microstructure change during the welding process. Shot peening contributed in the improvement of the bending strength for weld joint.